Gemcitabine in combination with epibrassinolide enhanced the apoptotic response in an ER stress-dependent manner and reduced the epithelial-mesenchymal transition in pancreatic cancer cells - Obakan Yerlikaya, Pınar; Mehdizadehtapeh, Leila; Rencüzoğulları, Özge; Kuryayeva, Fadina; Çevikli, Sena Sedef; Özağar, Şevval; Odabaş, Sibel Pınar; Tunçkol, Sude; Yetim, Hakan; Çoker Gürkan, Ajda; Arısan, Elif Damla (TUBITAK, 2022)
Gemcitabine is a broad-spectrum antimetabolite and a deoxycytidine analog recognized as a standard therapy alone or in combination with other antineoplastic agents in the therapy of pancreas cancer. Drug resistance following gemcitabine treatment is a common phenomenon; therefore, combinational therapy models are usually preferred. Pancreatic ductal adenocarcinoma, or pancreas cancer, is the fourth leading cause of cancer-related deaths worldwide. With the increasing incidence of pancreatic cancer every year, the mortality rate is also rising significantly because of late diagnosis, and limited chemotherapy options. Adjuvant chemotherapy after surgical resection is the typical option for the treatment of early pancreatic cancer. Mostly, 5-fluorouracil/leucovorin with irinotecan and oxaliplatin (FOLFIRINOX) and gemcitabine/nab-paclitaxel is used for the prognosis of advanced pancreatic cancer; however, chemoresistance usually occurs limiting the effectiveness of the chemotherapy. Therefore, most of the studies are focused on gemcitabine combination with other drugs to overcome the situation. As an apoptotic agent and a member of brassinosteroids, epibrassinolide (EBR) induces endoplasmic reticulum (ER) stress-dependent cell death in different cancer cells, as shown by our group. In this study, we aimed to enhance the gemcitabine apoptotic effect by EBR combined treatment in pancreatic cancer cells. EBR treatment reduced cell viability and inhibited cell proliferation in PANC-1, MIA PaCa-2, and AsPC-1 cells. Each pancreatic cancer cell gave different responses to the EBR treatment because of different aggressiveness. However, EBR induced apoptosis through increasing ROS generation, which was associated with ER stress in PANC-1 and MIA PaCa-2 cells. Gemcitabine alone reduced the cell viability of each pancreatic cancer cell line; however, combination with EBR led to further induction of apoptotic cell death in each pancreatic cancer cell line. In addition, combined treatment of gemcitabine and EBR further decreased N-cadherin and vimentin expressions, suggesting that epithelial-mesenchymal transition of pancreatic cells is reduced. In conclusion, EBR had therapeutic potential to avoid the gemcitabine-induced side effects during the treatment of pancreatic cancer.
We are thankful to TUBITAK (The Scientific and Technological Research Council of Turkey) 2209 Program for supporting this study.
Keywords: Endoplasmic reticulum stress; Epibrassinolide; Gemcitabine; Pancreatic cancer